Percepção e tecnologia : a escuta em interação com os dispositivos tecnológicos - Cremonez, Bruno Henrique (2017)
The objective of this work is to analyze the current relationship that emerges from the coupling between human beings and the technological devices related to listening, considering changes that occur in these devices mainly from the end of the 20th century and beginning of the 21st century, such as miniaturization and proliferation. For the proposed analysis, we map the term technology, which reveals that there is a set of dynamic and non-linear forces acting behind each of these devices, opening a field for dialogical interactions between human and machine. We also map out the theories of listening that emerged in the twentieth century that spring from this dialogical relationship with technology or that take it into account in order to establish a field for thinking about what is at stake in these theories. We conclude the study with an analysis on the relationship between the listening and one of the most established sound devices currently: the smartphone.